The fractionation and characterisation of lipid foulants adsorbed onto ultrafiltration membranes during contact with abattoir effluent - Cyster, Heidi (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1999.